The culture of samizdat : literature and underground networks in the late Soviet Union - von Zitzewitz, Josephine (London : Bloomsbury Academic, 2021)
"By analysing the periodicals produced in late Soviet Leningrad, The Culture of Samizdat makes use of oral and written testimonies to examine the role of Samizdat activists in late Soviet Russia. Crucially, as well as providing new insight into Samizdat texts, the book employs an interdisciplinary theoretical approach which draws on both the sociology of reading and book history. In doing so, von Zitzewitz uncovers the importance of 'middlemen' - including editors, readers and typists - in the Samizdat subculture"--
Introduction -- Samizdat: A Culture of Readers and Networks -- Readers: An Online Survey for Samizdat Readers -- Manufacturists: Samizdat Typists -- Collectors: Samizdat Libraries -- Patrons: Samizdat Journal Editors -- Institutions: Literary Samizdat and Official Culture -- Conclusion.
Includes bibliographical references and index.
Keywords: Underground literature -- Soviet Union -- History and criticism; Underground press publications -- Soviet Union -- History; Underground literature -- Publishing -- Soviet Union -- History; Dissenters -- Soviet Union; Books and reading -- Soviet Union